(untitled) (Research, Society and Development, 2023)
The objective of this work was to develop a mobile system and a web system to improve quality and processes in the food industry. The native language for the development of the mobile system was JAVA, using the Android studio operating platform, version 3.4 in the mobile system. In the web system, the native language was React, using the Visual Studio Code development platform, version 1.25.1. The developed systems portray two modules. The first module runs on a mobile device and was responsible for collecting data from employees of a food industry that works with indicators. Upon completion of the tests, the system automatically sends the data to an online server that stores it in the Firebase database, which can only be accessed online since it is hosted in the cloud. The second module is aimed at the industry manager, so that he can visualize the data and manage the company through tests and statistical methods, in the way that only he can register new employees, among other features. The use of the mobile system for the acquisition and statistical treatment of data from indicators in the food industry can be used in several industries to aid in the development and analysis of new ones, in quality control, in company management and with efficient decision making and fast. The developed system is important with regard to environmental sustainability by extinguishing the use of paper forms, as it can be used on tablets, smartphones and computers.